The Implementation of Legal Responsibilities Of Notary on Authentic Deed Which His Made Based On Act No. 2 of 2014 On the Amendment of Act No. 30 of 2004 On Notary in Kendari - Zahren Zukri Alyafie; Andi Kusuma Mapareppa; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
This study aims 1) To determine the implementation of the Civil Liability of the Deed Notary in Authentic are made according to Act No. 2 of 2014 on the Amendment of Act No. 30 of 2004 On Notary in Kendari; 2) To determine the barriers and solutions in the Implementation Responsibility Against Notary Authentic Deed had made in Kendari.This study uses empirical juridical approach, the specification of this research is descriptive. The type of data in this study include primary data and secondary data. Data obtainedthe method of interview and literature. Data analysis technique is qualitative.Based on this study concluded that: 1)Implementation of the Notary in Civil Responsibility of the Authentic Deed Which His Made, notary only responsible for the formal correctness of an Authentic Deed and not to the authentic deed material. The legal basis used in civil liability against the deed made by Notary Public Notary is if make mistakes because of broken promises as determined under the provisions of Article 1234 of the Civil Code and against the law as stipulated in the provisions of Article 1365 of the Civil Code. 2) Obstacles and Solutions in Implementation of Notary Responsibility of the Authentic Deed Which His Made, namely: a) Obstacles in the Implementation Responsibility The Notary of the Authentic Deed he made, when one of the parties then feel there are disadvantaged in this regard is the responsibility of the parties is not the responsibility of the notary. Precisely deed made by the notary is evidence that can be used by the parties. b) Solutions in the Implementation of Notary Responsibility of the Authentic Deed Which His Made If proved, no offense will be undertaken by the notary and harm either party in because a deed in him. The civil claims against the notary concerned civilly liable if proven.Keywords: Legal Responsibilities; Notary Public; Authentic Deed.